2020
DOI: 10.1159/000508809
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Intermediate-Stage Hepatocellular Carcinoma Patients Receiving Transarterial Chemoembolization prior to Designing Clinical Trials

Abstract: Background: Intermediate-stage hepatocellular carcinoma (HCC) has a high frequency of recurrence and progression to advanced stage after transarterial chemoembolization (TACE), particularly in patients with high tumor burden. Promising new results from immune checkpoint inhibitors (ICIs) and ICI-based therapies are expected to replace TACE, especially in HCC patients with high tumor burden. Aims: The present study aimed to evaluate the effectiveness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Patients who were beyond up-to-seven criteria were defined as: largest tumor diameter (cm) + number of tumors >7. 26 Progression-free survival (PFS) was calculated from the date of diagnosis to the date of tumor progression and tumor progression was assessed based on the 2019 version of Response Evaluation Criteria in Cancer of the Liver (RECICL), which was defined as tumor enlargement of ≥50%, excluding the area of treatment-induced necrosis in either target lesion or non-target lesion. 27 Overall survival (OS) was calculated from the date of diagnosis to the date of death due to any reason or to the date of the last followup.…”
Section: Response Evaluation and Follow-upmentioning
confidence: 99%
“…Patients who were beyond up-to-seven criteria were defined as: largest tumor diameter (cm) + number of tumors >7. 26 Progression-free survival (PFS) was calculated from the date of diagnosis to the date of tumor progression and tumor progression was assessed based on the 2019 version of Response Evaluation Criteria in Cancer of the Liver (RECICL), which was defined as tumor enlargement of ≥50%, excluding the area of treatment-induced necrosis in either target lesion or non-target lesion. 27 Overall survival (OS) was calculated from the date of diagnosis to the date of death due to any reason or to the date of the last followup.…”
Section: Response Evaluation and Follow-upmentioning
confidence: 99%
“…The radiological data included tumor distribution (unilobar/bilobar), number of tumors (solitary/2–3/>3), size of the largest tumor, and up-to-seven criteria (within/beyond). Patients who were beyond up-to-seven criteria was defined as: largest tumor diameter [cm] + number of tumors >7 ( Mazzaferro et al, 2009 ; Koroki et al, 2020 ). Radiological data were independently reviewed by two radiologists with either 22 or 19 years of experience of abdominal imaging, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…TACE is not a radical treatment, which may lead to poor results such as deterioration of liver function and extrahepatic metastasis 186 , 187 . Koroki K et al studied and evaluated the therapeutic effect of TCAE in patients with medium-term HCC 186 .…”
Section: Localized Treatments In Hccmentioning
confidence: 99%
“…TACE is not a radical treatment, which may lead to poor results such as deterioration of liver function and extrahepatic metastasis 186 , 187 . Koroki K et al studied and evaluated the therapeutic effect of TCAE in patients with medium-term HCC 186 . Studies had shown that the results of TACE in patients with medium-term HCC were closely related to the number and size of tumors.…”
Section: Localized Treatments In Hccmentioning
confidence: 99%